Vat-based 3D-bioprinted scaffolds from photocurable bacterial levan for osteogenesis and immunomodulation - Waidi, Yusuf Olatunji; Wagh, Vasudev S.; Mishra, Shivangi; Jhunjhunwala, Siddharth; Dastager, Syed G.; Chatterjee, Kaushik (Biomacromolecules, 2025)
Emerging techniques of additive manufacturing, such as vat-based three-dimensional (3D) bioprinting, offer novel routes to prepare personalized scaffolds of complex geometries. However, there is a need to develop bioinks suitable for clinical translation. This study explored the potential of bacterial-sourced methacrylate levan (LeMA) as a bioink for the digital light processing (DLP) 3D bioprinting of bone tissue scaffolds. LeMA was successfully synthesized, characterized, and used to fabricate 3D-bioprinted scaffolds with excellent printability and physicochemical properties. In vitro studies demonstrated superior cytocompatibility of 15% w/v LeMA gels compared to 20% gels. 15% LeMA gels supported osteogenic differentiation , as evidenced by alkaline phosphatase activity and mineral deposition by MC3T3 pre-osteoblasts. Importantly, the LeMA hydrogels positively modulated the macrophage phenotype, promoting the expression of the anti-inflammatory marker CD206. These findings suggest that 3D-printed LeMA scaffolds can create a favorable microenvironment for bone regeneration, highlighting their potential for tissue repair and regeneration applications.